Tumor Microenvironment Adaptable Nanoplatform for O2 Self‐Sufficient Chemo/Photodynamic Combination Therapy. (19th February 2020) - Li, Shi‐Ying; Zhao, Lin‐Ping; Zheng, Rong‐Rong; Fan, Gui‐Ling; Liu, Ling‐Shan; Zhou, Xiang; Chen, Xian‐Tong; Qiu, Xiao‐Zhong; Yu, Xi‐Yong; Cheng, Hong
Abstract: Malignant proliferation of tumor cells induces abnormal tissue microenvironments, leading to therapeutic resistance and poor therapeutic outcome. In this paper, manganese dioxide (MnO2 ) nanoshells are coated on a porphyrinic metal–organic framework of porous coordination network (PCN)‐224 for doxorubicin (DOX) loading and hyaluronic acid (HA) modification to obtain an intelligent nanoplatform of PCN@MnO2 @DOX@HA (PMDH). Benefiting from the HA functionalization, PMDH prefers to accumulate in tumor sites and enhance the cellular uptake by CD44‐overexpressed tumor cells. Subsequently, the internalized PMDH could catalyze the abundant H2 O2 in cells into O2 to relieve tumor hypoxia. Further, the MnO2 nanoshells of PMDH could be degraded into Mn 2+ for magnetic resonance imaging with glutathione reduction and the release of DOX. By integrating the O2 self‐sufficiency with glutathione reduction abilities, PMDH possesses highly potent chemo/photodynamic combination therapeutic effects against hypoxic tumors. Significantly, PMDH exhibits a good biocompatibility with a low cardiotoxicity and negligible systemic side effects, which provides a new insight in developing tumor microenvironment adaptable nanoplatforms for synergistic tumor theranostics. Abstract : A manganese dioxide (MnO2 )‐coated porphyrinic metal–organic framework is prepared for doxorubicin (DOX) loading and hyaluronic acid (HA) modification to construct an intelligent nanoplatform of PCN@MnO2@DOX@HA (PMDH). Under tumor microenvironment, PMDH achieves effective drug release, glutathione consumption, and O2 self‐sufficiency for magnetic resonance imaging–guided chemo/photodynamic combination therapy against hypoxic tumor.